2013
DOI: 10.1039/c2ce26126j
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular architecture of molecular crystals possessing shearing mechanical properties: columns versus layers

Abstract: The supramolecular architectures of crystals of substituted benzenes possessing shearing mechanical properties have been analyzed from the viewpoint of energy of intermolecular interactions. It is demonstrated that suggested earlier layered structure of these crystals do not correspond to the character of intermolecular interactions. Analysis of the topology of intermolecular interactions indicates that the crystals have a columnar supramolecular architecture with weak interactions between the columns. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 26 publications
2
22
1
1
Order By: Relevance
“…54 (We note that the interaction energies reported in ref. 52 for HCB are all $25% greater than the present CE-B3LYP results, but we cannot identify the origin of this difference).…”
Section: Faraday Discussion Papercontrasting
confidence: 78%
See 1 more Smart Citation
“…54 (We note that the interaction energies reported in ref. 52 for HCB are all $25% greater than the present CE-B3LYP results, but we cannot identify the origin of this difference).…”
Section: Faraday Discussion Papercontrasting
confidence: 78%
“…51 HBB is isostructural with HCB but, unlike HCB, it only exhibits bending at elevated temperatures ($400 K). 48 These studies acknowledge the strongly anisotropic intermolecular interactions that are responsible for the mechanical behaviour of HCB, and although this anisotropy has been quantied for HCB using counterpoise- corrected BLYP-D/def2-TZVP energies for molecular pairs, 52 no comparison has been made with HBB. Here we use CE-B3LYP model energies, and the separate electrostatic and dispersion contributions, to investigate the interaction anisotropy in HCB and HBB using energy framework diagrams (Fig.…”
Section: Faraday Discussion Papermentioning
confidence: 99%
“…[36][37][38][39][40][41] It is important to note that even though evolution of dislocations was not reported to occur it does not mean it did not occur. [36][37][38][39][40][41] It is important to note that even though evolution of dislocations was not reported to occur it does not mean it did not occur.…”
Section: Plastic Bending Without Delaminationmentioning
confidence: 99%
“…20 For example, Shishkin et al concluded that the basic structural motif of substituted 1,3,5-trihalobenzenes is not a halogen bonded layer, but a strongly bonded stacked column. The present energy frameworks are less computationally demanding than energy-vector diagrams, and rather more self-explanatory.…”
mentioning
confidence: 99%